2019
DOI: 10.3390/w11081645
|View full text |Cite
|
Sign up to set email alerts
|

Post-Treatment of Nanofiltration Polyamide Membrane through Alkali-Catalyzed Hydrolysis to Treat Dyes in Model Wastewater

Abstract: This research focused on the influence of post-treatment using alkali-catalyzed hydrolysis with a full-aromatic nanofiltration (NF) polyamide membrane and its application to the efficient removal of selected dyes. The post-treated membranes were characterized through Fourier transform infrared spectroscopy, goniometry, and zeta-potential analysis to analyze the treatment-induced changes in the intrinsic properties of the membrane. Furthermore, the changes in permeability induced by the post-treatment were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…This technology is based on the separation of compounds by size and charge, as the membrane acts as a filter that retains the molecules which are larger than the pore and allows the water to pass through. In the last decade, more than 65% of research works have been based on the fabrication strategies of nanoporous membranes and their applications in the field of water purification [ 7 , 8 , 9 , 10 , 11 , 12 ]. According to Wang et al the solute and water permeability play important roles in the membrane performance.…”
Section: Introductionmentioning
confidence: 99%
“…This technology is based on the separation of compounds by size and charge, as the membrane acts as a filter that retains the molecules which are larger than the pore and allows the water to pass through. In the last decade, more than 65% of research works have been based on the fabrication strategies of nanoporous membranes and their applications in the field of water purification [ 7 , 8 , 9 , 10 , 11 , 12 ]. According to Wang et al the solute and water permeability play important roles in the membrane performance.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that an alkali-catalyzed hydrolysis PA membrane was observed after post-treatment at pH 14 for 28 days [ 26 ]. Herein, PA6 PNM was kept in NaOH for 24 h, which did not show any changes.…”
Section: Resultsmentioning
confidence: 99%
“…Under extreme pH conditions, the structure of amide bonds in polyamide can be easily destroyed by an acid or base. Since hydrogen or hydroxide ions react with oxygen/nitrogen or carbon atoms in amide bonding, this can abate the resonance structure of an amide and cause hydrolysis of the amide bond [ 26 ]. Moreover, under strong acidic and alkaline conditions, the charged groups in the membrane matrix can cause internal charged repulsion, resulting in expansion of the membrane structure and pores.…”
Section: Resultsmentioning
confidence: 99%
“…In general, no obvious peculiarities were visible in the diagrams, except for the significant change in the intensities of the O-H band in the 3000-3680 cm −1 region between the TFC FOs and their support membranes. It is postulated that the increases in intensity may have helped increase the surface hydrophilicities of the TFC FO membranes, as evidenced by the CA measurements, that is, MS2 > MS1 > MS3 [34,35]. The weak peaks observed at 1660 cm −1 and 1550 cm −1 in TFC FO membranes correspond to amide I (C = O stretching) and amide II (N-H bending), both due to the formation of product groups during the IP reaction.…”
Section: Effect Of the Psf:pes Ratios On The Functional Group Analysis Of The Pa Layermentioning
confidence: 93%